1989
DOI: 10.1007/bf00265549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotinamide treatment on the residual insulin secretion in Type 1 (insulin-dependent) diabetic patients

Abstract: In vivo and in vitro experiments have shown that nicotinamide enhances the regeneration of rat B cells. Nicotinamide has been administered to human subjects at a dose of 3 g/day for more than one year without any serious side effects. A trial was conducted to study if nicotinamide could protect B cells in Type I (insulin-dependent) diabetic patients with established diabetes, but still with residual insulin secretion, the latter being evaluated throughout the study period. A randomized double-blind study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 31 publications
2
33
0
7
Order By: Relevance
“…Administration of nicotinamide prevents rodent diabetes after STZ administration (22) and also blocks the development of diabetes in the nonobese diabetic mouse, a model of spontaneous autoimmune diabetes (42). This nontoxic agent has displayed some limited beneficial effects in human diabetes (43)(44)(45)(46) and is currently being evaluated as a prophylactic agent in first degree relatives of type I diabetic patients possessing islet cell antibodies (47).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of nicotinamide prevents rodent diabetes after STZ administration (22) and also blocks the development of diabetes in the nonobese diabetic mouse, a model of spontaneous autoimmune diabetes (42). This nontoxic agent has displayed some limited beneficial effects in human diabetes (43)(44)(45)(46) and is currently being evaluated as a prophylactic agent in first degree relatives of type I diabetic patients possessing islet cell antibodies (47).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nicotinamide was effective in preventing diabetes mellitus in NOD mice and possibly in human Type I diabetes mellitus [24,25,52]. Nicotinamide has also been shown to reduce the downstream signals of IFNg such as IRF-1 in isolated rat pancreatic islets [22].…”
Section: Discussionmentioning
confidence: 99%
“…Older clinical studies using nicotinic acid or impure preparations of nicotinamide reported relatively frequent liver enzyme abnormalities [6, 33±35] although more recent studies using a purified form of nicotinamide have not detected any noteworthy adverse effects on liver enzymes [13,15,17,20,36]. This experience is described in more detail below.…”
Section: Liver Toxicitymentioning
confidence: 95%